Utilization and Prescribing Pattern of Rivaroxaban in a Large Teaching Hospital in Iran: Drug Utilization Evaluation of Rivaroxaban - Mousavi, Sarah; Saffari, Mohadeseh; Hakiminia, Bahareh; Amirsadri, Mohammadreza; Ansari, Narges (Iranian Journal of Pharmaceutical Sciences, 2021)
This medication utilization evaluation aims to describe the use of rivaroxaban in a tertiary care teaching hospital and to audit the hospital physician’s prescribing practice. A prospective cross-sectional study was performed from March to December 2019 in Alzahra teaching hospital, Isfahan, Iran. All patients who received at least one dose of rivaroxaban were eligible for inclusion. Data were collected on patient demographics, indication, dosing regimen, adverse events, concurrent anticoagulant therapy, and laboratory tests (including renal function). A total of 104 patients were included in our study. Most patients (N=39, 37.5%) were prescribed rivaroxaban for deep vein thrombosis (DVT) prophylaxis. Overall, more than 34% of rivaroxaban prescriptions was appropriate. Rivaroxaban was indicated correctly in all the patients (100% appropriate indication). However, 58.6% and 50% of patients received correct dosing, respectively, based on indication and renal function. High-dose prescribing was the major fault of prescriptions when the renal function was taken into account (82.6%). An appropriate switch occurred in 48.7% of the patients who switched from one anticoagulant to another. Inappropriate prescription of rivaroxaban for many patients in the current study emphasizes the requirement of developing a scientifically well-defined protocol for the use of rivaroxaban in the evaluated hospital. Accordingly, establishing a structured educational program for prescribers and assigning the rivaroxaban prescription to specialized services with consultation with clinical pharmacists is recommended.